Interaction Hypersurfaces Applied to Estimate the Load-Carrying Capacity of Space Trusses - König, J.A.; Karczewski, J.A.; Czarnecki, J. (Engineering Transactions, 1988)
When determining the load-carrying capacity of a space truss, one has assumed, usually that the result depends exclusively on properties of elements (struts) i. e. that the strengh of joints is sufficiently high. Since joints constitute up to 30 per cent of the total truss weight such an approach seems non-economical. The paper presents another approach to the joints design based on analysis of their strength by means of interaction hypersurfaces of forces acting upon them. First, the general concept is outlined and, then, possible simplifications are shown in the case of joint and load symmetries. The theoretical considerations are illustrated by a numerical example of a truss plate. Some general conclusions considering further development of the proposed approach are given.